Thickness determination of semitransparent solids using flash thermography and an analytical model. Issue 1 (2nd January 2018) - Altenburg, S. J.; Weber, H.; Krankenhagen, R.
Abstract: As groundwork for thickness determination of polymeric surface protection systems for concrete, we present a method for measuring the thickness of isolated semitransparent solids using flash thermography both in transmission and reflection configuration. Since standard models do not capture semitransparency, an advanced analytical model by Salazar et al. is applied. Physical material parameters are deduced by fitting experimental data from samples of well-known thickness. Using those, the thickness of samples of the material can be obtained by fitting, as demonstrated for different semitransparent polymer materials.